The secrets of Tutankhamun : Egypt's boy king and his incredible tomb - Cleveland-Peck, Patricia (Bloomsbury, 2018)
Presents an illustrated exploration of the life of Egypt's King Tutankhamun. Highlights the discovery of King Tut's tomb and the treasures found within it.